Global research landscape and science mapping of age-friendly communities: A bibliometric analysis on healthy aging and community resilience (2015–2025) - Sukardin Sukardin; Milya Novera; Sumana Lama; Omawale Odoyemi; Altaf Hussain (Nurse Point: Journal of Nursing, 2026)
Background: The global demographic transition underscores the necessity for the development of Age-Friendly Communities (AFCs) aimed at promoting healthy ageing and enhancing community resilience. This study examines the intellectual framework surrounding AFC research from 2015 to 2025, to inform nursing scholarship and public health initiatives. Methods: A comprehensive bibliometric analysis was performed on 245 peer-reviewed articles obtained from the Scopus database, covering the timeframe from 2015 to 2025. This targeted selection adhered to stringent inclusion criteria that emphasize the direct intersection of four key domains: "older adults," "community resilience," "healthy ageing," and "age-friendly communities." The analysis incorporated performance metrics, science mapping, and visualizations using the VOSviewer. Results: Research output saw significant growth post-2020, with a CAGR of over 15%, driven by the United Nations Decade of Healthy Ageing. While the US, UK, Canada, and Australia (the 'QUAD' group) have historically led in research, East Asian nations, especially China and Japan, are experiencing the fastest growth. The focus in AFC research has shifted from the Built Environment and Policy Adoption to include Digital Inclusion, Community Resilience, and Health Equity. Notably, Nursing Science is gaining importance, with a focus on translational interventions such as intergenerational reminiscence programs and community care models. Conclusion: The field of AFC research is progressing swiftly, with a shift towards data-driven and comprehensive analyses. The findings highlight an urgent need for nursing-led community interventions, especially those that incorporate intergenerational approaches and AFC principles, to address health disparities and enhance resilience among vulnerable older adults worldwide. This underscores the critical role of nursing as a leading discipline in addressing these important issues.